Alteração da carga de ectoparasitas e das propriedades organolépticas do leite de vacas da raça holandesa submetidas a diferentes níveis de alho na alimentação - Massariol, Péricles Boechat (2008)
Sixteen lactating Holstein cows were used to evaluate the effect of suply of garlic in the feed on the alteration of load of tick, horn fly and stably fly and domestic fly. The treatments were garlic at 100g (A100) and 200g cow-1 (A200) for three days, Amitraz at 0.025% (Am) and negative control group. Engorged ticks were evaluated with lengh superior to 4.0 mm and flys before and at 1st, 2nd, 3rd, 4th, 5th, 6th, 7th, and 14thday after treatment. In the 1st, 2nd, 3rd days after treatments, milk samples were taken for flavor evaluation on raw milk and soft cheese Minas-Frescal. The efficacy of treatments were 27.34; 12.31; e 97.05% for (A100), (A200) e (Am), respectively. Commercial ectoparasiticide was more efficacious in the control of ticks. Garlic show low efficacy on control tick and inefficacious in control of flies. In these treatments, no residual garlic flavor or taste was detected on milk and cheese.